2016
DOI: 10.1038/srep36179
|View full text |Cite
|
Sign up to set email alerts
|

Global functional profiling of human ubiquitome identifies E3 ubiquitin ligase DCST1 as a novel negative regulator of Type-I interferon signaling

Abstract: Type I interferon (IFN-I) mediated innate immune response controls virus infections by inducing the expression of interferon stimulated genes (ISGs). Although ubiquitination plays key roles in immune signaling regulation, a human genome-wide understanding of the role of E3 ubiquitin ligases in interferon mediated ISG induction is lacking. Here, we report a genome-wide profiling of the effect of ectopic expression of 521 E3 ubiquitin ligases and substrate recognition subunits encoded in the human genome (which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…To investigate the hypothesis that decreases in the relative expression of interferon-associated genes may explain increased susceptibility of RA-differentiated versus undifferentiated SH-SY5Y cells to ZIKV infection, we analyzed the transcriptome profiling data for levels of expression of interferon-stimulated genes (ISGs). We did not observe down-regulation of ISGs in differentiated cells; rather, genes associated with type I interferon signaling, such as IRF9 and STAT2, were up-regulated in RA-differentiated cells, and the only significantly down-regulated gene identified, DSCT1, was a negative regulator of type I interferon signaling 37 . This suggested that the enhanced ZIKV infection in RA-differentiated cells was not due to basal decreases in the expression of ISGs.…”
Section: Resultscontrasting
confidence: 72%
“…To investigate the hypothesis that decreases in the relative expression of interferon-associated genes may explain increased susceptibility of RA-differentiated versus undifferentiated SH-SY5Y cells to ZIKV infection, we analyzed the transcriptome profiling data for levels of expression of interferon-stimulated genes (ISGs). We did not observe down-regulation of ISGs in differentiated cells; rather, genes associated with type I interferon signaling, such as IRF9 and STAT2, were up-regulated in RA-differentiated cells, and the only significantly down-regulated gene identified, DSCT1, was a negative regulator of type I interferon signaling 37 . This suggested that the enhanced ZIKV infection in RA-differentiated cells was not due to basal decreases in the expression of ISGs.…”
Section: Resultscontrasting
confidence: 72%
“…These findings further demonstrated that DCST1 promoted conjugation of only the K48 lysine containing ubiquitin to STAT2. This conjugation indicates that it promotes K48 ubiquitination of STAT2 (34). Although recent studies have evaluated STAT stability regulation, the molecular mechanisms and E3 ubiquitin ligase for STATs are largely unknown.…”
Section: Discussionmentioning
confidence: 98%
“…These proteins have been shown to be overexpressed in several types of cancer, including melanoma, gastrointestinal tumors, lymphoma, and pancreatic cancer, thereby playing an active role in cancer promotion [141][142][143][144][145][146]. Likewise, the ubiquitin ligase DCST1 is able to induce ubiquitination and degradation of STAT2, which results in hampered type I IFN signaling and has also been shown to be elevated in various cancers [147]. The small molecule inhibitors PRT4165 and A01 successfully inhibit, respectively, RNF2 and Smurf1 in vitro [148,149].…”
Section: Negative Regulators Of Ifn Signalingmentioning
confidence: 99%